ANALISIS SALURAN PEMASARAN KERIPIK GADUNG (Dioscorea hispida L.) PADA USAHA HOME INDUSTRY DUA PUTRA JAYA DI KABUPATEN JOMBANG - Muhammad Amir Ma'sum; Umi Kulsum Nur Qurmariah (Sigmagri, 2021)
This study aims to determine the form of marketing channels, marketing margins, share of the price received by producers and marketing efficiency of gadung chips in the "Dua Putra Jaya" home industry in Jombang Regency. This study uses a quantitative descriptive method. Determination of sampling is done purposively. Respondents include producers, retailers, collectors, and consumers. Data were obtained from direct observation in the field through interviews, distributing questionnaires and tracing. The results showed that the marketing channel for Gadung chips "Dua Putra Jaya" consists of three marketing channels, namely; zero-level channels consist of producers (consumers, Level 1 channels consist of producers( retailers (consumers; Level 2 marketing channels consist of producers( collectors( retailers( consumers. The total margin on the zero level channel is non existent, the level 1 marketing channel is IDR 20,000 and the level 2 marketing channel is IDR 20,000. The share of the price received by on the zero level channel does not exist, the price share on the level 1 channel is 75%; while the channel level 2 is 55.5%. There is no efficiency value in the zero level marketing channel, the marketing channel level 1 is 31.6% and the marketing channel level 2 is 35.5%, so that it can be seen that the marketing channel in channel one is more efficient because of the marketing costs incurred in channel one. less first.